2013
DOI: 10.1016/j.mrfmmm.2012.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for base excision repair processing of DNA interstrand crosslinks

Abstract: Many bifunctional alkylating agents and anticancer drugs exert their cytotoxicity by producing cross links between the two complementary strands of DNA, termed interstrand crosslinks (ICLs). This blocks the strand separating processes during DNA replication and transcription, which can lead to cell cycle arrest and apoptosis. Cells use multiple DNA repair systems to eliminate the ICLs. Concerted action of repair proteins involved in Nucleotide Excision Repair and Homologous Recombination pathways are suggested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 138 publications
(153 reference statements)
1
20
0
Order By: Relevance
“…The decrease in the crosslinking level is also possibly due to death of the cells containing high levels of DNA damage. Moreover, besides the AGT‐mediated repair mechanism, there are other pathways repairing the crosslinked base pair, such as the base excision repair (BER) processing, in which the BER proteins are capable of recognizing and removing the crosslinked base pairs induced by chemotherapeutic agents …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in the crosslinking level is also possibly due to death of the cells containing high levels of DNA damage. Moreover, besides the AGT‐mediated repair mechanism, there are other pathways repairing the crosslinked base pair, such as the base excision repair (BER) processing, in which the BER proteins are capable of recognizing and removing the crosslinked base pairs induced by chemotherapeutic agents …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, besides the AGT-mediated repair mechanism, there are other pathways repairing the crosslinked base pair, such as the base excision repair (BER) processing, in which the BER proteins are capable of recognizing and removing the crosslinked base pairs induced by chemotherapeutic agents. [41] Ueda-Kawamitsu et al [14] performed a quantitative analysis of BCNU-induced dG-dC crosslinks in L1210 leukemia cells by fluorescence assay with BCNU exposure for 24 h. The results indicated that the maximum level of DNA ICL was observed at 6 h followed by a decline, which was attributed to the repair mechanism. Both of the two studies gave direct evidence for the AGT-mediated repair of DNA ICLs by observing obvious decreases in the crosslinking levels, although different peak times of the crosslinking levels were observed.…”
Section: Quantitation Of Dg-dc Crosslinks In the Hydrolysates Of Acnumentioning
confidence: 99%
“…In another set of studies, it was found that the deletion of the BER proteins Pol β and uracil DNA glycosylase (UNG) conferred resistance to cisplatin toxicity [90]. This led to a proposal that UNGs remove uracil residues generated by deamination of cytosine residues near cisplatin cross-links, thus inhibiting subsequent repair [91]. In a final early example where BER may influence the repair of cross-links, Couvé et al showed that NEIL1 can excise an unhooked, psoralen-derived cross-link remnant from a three-stranded structure (e.g.…”
Section: Base Excision Repair Dna Glycosylases and Their Involvemementioning
confidence: 99%
“…However, in the case of ovarian cancer, no significant difference was found between APE1 expression in platinum sensitive and platinum refractory cancers [9]. Targeting APE1 has been shown to mediate sensitivity to DNA damaging agents such as BCNU and MMC [10, 11]. Accumulation of abasic sites and subsequent generation of DNA double strand breaks (DSBs) are likely responsible for this cellular sensitivity.…”
Section: Introductionmentioning
confidence: 99%